Screening, identification and bioactive properites of Bacillus spp. isolated from shrimp ponds of Quang Tri province - Cuc, Nguyen Thi Kim; Cuong, Pham Viet (Vietnam Journal of Science and Technology, 2015)
Aquaculture is the farming of aquatic organisms by intervention in the rearing process to enhance production and private ownership of the stock being cultivated. However, the intensiﬁcation of aquaculture practices requires cultivation at high densities, which has caused signiﬁcant damage to the environment and , aquatic species are subjected to high-stress conditions, increasing the incidence of diseases and causing a decrease in productivity. This study was conducted to isolate bacteria from sediments of shrimp culture ponds based on antagonistic activity against shrimp pathogen, Vibrio parahaemolyticus, and production of exocellular enzymes, protease and amylase. Three potential strains were isolated and after analysis of 16S rRNA gene, the isolated starin were identified to Bacillus subtilis (isolate QTA12 with amylase activity), Bacillus megaterium (QTP1 with proteolytic activity ) and Bacillus subtilis (isolate with antivibrio activity DK1). These isolated strains may be considered for future using in shrimp culture ponds as a very promising measure for sustainable aquaculture.